Metastability of Nonreversible Random Walks in a Potential Field and the Eyring‐Kramers Transition Rate Formula. Issue 2 (26th October 2017) - Landim, Claudio; Seo, Insuk
Abstract : We consider nonreversible random walks in a bounded domain of ℝ d evolving on a potential field. We describe the complete metastable behavior of the random walk among the landscape of valleys, and we derive the Eyring‐Kramers formula for the mean transition time from a metastable set to a stable set.© 2017 Wiley Periodicals, Inc.